Pemberdayaan Masyarakat Desa Dalam Mendukung Pendidikan Dasar Berkualitas di Desa Pikatan - Khoiruzzaim Kurniawan; Muhammad Soni Amrulloh; Abu Zaeni; Andressa Muthi Latansa; Mega Dwi Susanti (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
Basic education in rural areas still faces significant challenges related to low student literacy and numeracy skills, as well as minimal parental participation. This study aims to analyze the effectiveness of community empowerment through the "Trisinergi" model (school, family, and community) in supporting quality basic education in Pikatan Village. Using a qualitative approach with the Participatory Action Research (PAR) method, this study involves teachers, parents, and community leaders as subjects of empowerment. Data were collected through participant observation, in-depth interviews, and documentation. The results indicate that interventions in the form of strengthening teachers' pedagogical capacity and providing parenting education successfully increased parental involvement by 60% and the effectiveness of teaching strategies by 62.5%. The direct impact of this synergy was an increase in students' literacy skills by 44.4% and numeracy by 38.7%. This study concludes that the utilization of social capital and the integration of roles between the three educational pillars are key factors in creating an inclusive, independent, and sustainable educational ecosystem at the village level.